Field notes contributed by Stephen J. Dinsmore, summer 1991 - Dinsmore, Stephen J.et al (1991)
List of birds and locations contributed by Stephen J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of summer 1991. Epson - sheet feed